Noise-induced hearing loss vulnerability in type III intermediate filament peripherin gene knockout mice - Cederholm, Jennie M. E.; Parley, Kristina E.; Perera, Chamini J.; von Jonquieres, Georg; Pinyon, Jeremy L.; Julien, Jean-Pierre; Ryugo, David K.; Ryan, Allen F.; Housley, Gary D. (Frontiers in Neurology, 2022)
In the post-natal mouse cochlea, type II spiral ganglion neurons (SGNs) innervating the electromotile outer hair cells (OHCs) of the ‘cochlear amplifier’ selectively express the type III intermediate filament peripherin gene (Prph). Immunolabeling showed that Prph knockout (KO) mice exhibited disruption of this (outer spiral bundle) afferent innervation, while the radial fibre (type I SGN) innervation of the inner hair cells (~ 95% of the SGN population) was retained. Functionality of the medial olivocochlear (MOC) efferent innervation of the OHCs was confirmed in the PrphKO, based on suppression of distortion product otoacoustic emissions (DPOAEs) via direct electrical stimulation. However, ‘contralateral suppression’ of the MOC reflex neural circuit, evident as a rapid reduction in cubic DPOAE when noise is presented to the opposite ear in wildtype mice, was substantially disrupted in the PrphKO. Auditory brainstem response (ABR) measurements demonstrated that hearing sensitivity (thresholds and growth-functions) were indistinguishable between wildtype and PrphKO mice. Despite this comparability in sound transduction and strength of the afferent signal to the central auditory pathways, high-intensity, broadband noise exposure (108 dB SPL, 1 hour) produced permanent high frequency hearing loss (24 kHz – 32 kHz) in PrphKO mice but not the wildtype mice, consistent with the attenuated contralateral suppression of the PrphKO. These data support the postulate that auditory neurons expressing Prph contribute to the sensory arm of the otoprotective MOC feedback circuit.